Methodology for Rapid Measures of Glutamate Release in Rat Brain Slices Using Ceramic-Based Microelectrode Arrays: Basic Characterization and Drug Pharmacology - Quintero, Jorge E. (2011)
Excessive excitability or hyperexcitability of glutamate-containing neurons in the brain has been proposed as a possible explanation for anxiety, stress-induced disorders, epilepsy, and some neurodegenerative diseases. However, direct measurement of glutamate on a rapid time scale has proven to be difficult. Here we adapted enzyme-based microelectrode arrays (MEA) capable of detecting glutamate in vivo, to assess the effectiveness of hyperexcitability modulators on glutamate release in brain slices of the rat neocortex. Using glutamate oxidase coated ceramic MEAs coupled with constant voltage amperometry, we measured resting glutamate levels and synaptic overflow of glutamate after K(+) stimulation in brain slices. MEAs reproducibly detected glutamate on a second-by-second time scale in the brain slice preparation after depolarization with high K(+) to evoke glutamate release. This stimulus-evoked glutamate release was robust, reproducible, and calcium dependent. The K(+)-evoked glutamate release was modulated by ligands to the a(2)δ subunit of voltage sensitive calcium channels (PD-0332334 and PD-0200390). Meanwhile, agonists to Group II metabotropic glutamate (mGlu) receptors (LY379268 and LY354740), which are known to alter hyperexcitability of glutamate neurons, attenuated K(+)-evoked glutamate release but did not alter resting glutamate levels. This new MEA technology provides a means of directly measuring the chemical messengers involved in glutamate neurotransmission and thereby helping to reveal the role multiple glutamatergic system components have on glutamate signaling.